TLR9 Mediated Tumor-Stroma Interactions in Human Papilloma Virus (HPV)-Positive Head and Neck Squamous Cell Carcinoma Up-Regulate PD-L1 and PD-L2 - Baruah, Paramita; Bullenkamp, Jessica; Wilson, Philip O. G.; Lee, Michael; Kaski, Juan Carlos; Dumitriu, Ingrid E. (Frontiers in Immunology, 2019)
Background: The co-inhibitory receptor PD-1 is expressed in many tumours including head and neck squamous cell carcinoma (HNSCC) and is an important immunotherapy target. However, the role of PD-1 ligands, PD-L1 and particularly PD-L2, in the tumour-stromal cell interactions that cause a tumour-permissive environment in HNSCC is not completely understood and is the focus of our study. Methods: Expression of PD-L1 and PD-L2 was analysed by immunohistochemistry in situ in HNSCC tumour tissue. Co-cultures were established between stromal cells (fibroblasts and macrophages) and human papilloma virus (HPV)-positive and HPV-negative HNSCC cell lines (HNSCCs) and PD-1 ligands expression was analysed using flow cytometry. Results: PD-L1 and PD-L2 were expressed both in tumour cells and stroma in HNSCC tissue in situ. In vitro, basal expression of PD-L1 and PD-L2 was low in HNSCCs and high on fibroblasts and macrophages. Interestingly, HPV-positive but not HPV-negative HNSCCs increased the expression of both PD-1 ligands on fibroblasts upon co-culture. This effect was not observed with macrophages. Conversely, both fibroblasts and macrophages increased PD-1 ligands on HPV-positive HNSCCs, whilst this was not observed in HPV-negative HNSCCs. Crucially, we demonstrate that up-regulation of PD-L1 and PD-L2 on fibroblasts by HPV-positive HNSCCs is mediated via TLR9. Conclusions: This work demonstrates in an in vitro model that HPV-positive HNSCCs regulate PD-L1/2 expression on fibroblasts via TLR9. This may open novel avenues to modulate immune checkpoint regulator PD-1 and its ligands by targeting TLR9.